Conselho de meio ambiente e efetividade deliberativa: avaliando o caso do município de Juazeiro do Norte/CE - Monte, Maykon Oliveira (2024)
Ever since the practices of political activity started being questioned, the limits of the representative regime have gained new contours. The idea that participation was capable of changing power structures by including new actors in decision-making was consolidated. In Brazil, this premise supported the formation of institutionalized management councils, innovative channels formed by representatives of civil society and the State. Over time, there has been no shortage of criticism of the emblematic actions of these bodies, both due to their internal functioning and external repercussions. Considering these aspects, this research aims to evaluate the degree of deliberative effectiveness of the Environmental Defense Council of the municipality of Juazeiro do Norte/Brazil (COMDEMA), between the years 1989 and 2019. Qualitative in nature and guided by ex-post facto evaluation, the work adopts utilizes this case study as outline, articulated with bibliographic and documentary research. The data analysus obeys the criteria of content analysis by classification and triangulation, incorporating elements that are constant in legislation, the statements recorded in minutes and the opinions of interviewees. In summary, the results achieved reveal that, although Juazeiro do Norte has consolidated environmental legislation, its COMDEMA manifests itself as a space led by the government and modest action by civil society. Furthermore, the decisions taken by the council follow the logic of control, that is, debating agendas already defined by other bodies, to the detriment of more purposeful action. In effect, this instance presented a low degree of deliberative effectiveness, following a trend seen in other studies on management councils. Although it is an institutionally well-intentioned body, its limited propositional capacity combined with low civil society performance reflect internal power disparities and the difficulty of producing broader public policy effects for the community.